FUNCTIONAL AND LABORATORY RESEARCH METHODS FOR URINARY TRACT DISEASES - Umarova T. A.; Kudratova Z. E.; Raupova U. (Web of Journals Publishing, 2025)
Instrumental methods of investigation are used to assess the anatomo-morphological and functional status of the kidney and urinary tract. These include radiologic and radionuclide methods, ultrasound and kidney biopsy.
Keywords: Kidney and urinary tract, renal morphologic examination, ultrasound and kidney biopsy, radiation.